Initial Results and Diurnal Variations Measured by a New Microwave Stratospheric ClO Instrument at Mauna Kea. Issue 18 (15th September 2020) - Nedoluha, Gerald E.; Gomez, R. Michael; Boyd, Ian; Neal, Helen; Parrish, Alan; Connor, Brian; Mooney, Thomas; Siskind, David E.; Sagawa, Hideo; Santee, Michelle
Abstract: We present the first year of ClO and O3 measurements from a new 278 GHz Chlorine monOxide Experiment (ChlOE) microwave instrument on Mauna Kea. We make use of comparisons with the Aura Microwave Limb Sounder (MLS) O3 measurements to recalibrate the ground‐based instrument and find that the recalibrated ground‐based O3 retrievals remain stable relative to MLS throughout the year. The MLS measurements provide daily daytime ( 1330 local solar time) and nighttime ( 0200 local solar time) ClO retrievals, and we find that the monthly ChlOE ClO retrievals show mixing ratios slightly smaller than those from MLS in the vicinity of Mauna Kea, with daytime values near the peak 6–8% lower at 30–45 km for the average of the 12 months in this study. The nighttime monthly ClO values are almost all within ±0.03 ppbv over most of this altitude range, with very little overall bias. We have also made detailed hourly diurnal O3 comparisons with a multiyear analysis of previous retrievals from the much stronger 110 GHz O3 emission line being measured by our instrument at Mauna Loa and find that the hour‐to‐hour differences are within ±2% at 40 km, which indicates that the overall calibration of the ChlOE instrument is stable relative to time of day. We show hourly diurnal variations of ClO and compare these to 2010 measurements from the Submillimeter‐Wave Limb‐Emission Sounder and to a model. Plain Language Summary: The chlorine atoms that reach the stratosphere due to emission of manmade chlorofluorocarbons are present in several molecular forms. The molecule most directly involved in ozone destruction is the chlorine monoxide (ClO), and the fraction of chlorine atoms in the form of ClO varies diurnally. During the day, the peak mixing ratio of ClO is at 38 km. Unlike most atmospheric measurements, ground‐based Chlorine monOxide Experiment (ChlOE) microwave instruments can, in good local conditions, provide continuous measurements at any time of day, and they are therefore able to sample the full diurnal cycle. The high altitude ( 4 km) of Mauna Kea provides the low tropospheric opacity that is a key to making successful ground‐based measurements of ClO. The measurements from the new ChlOE instrument described here will extend the ClO measurements time series from which trends have been calculated since 1995. The new instrument allows for the simultaneous measurement of ozone, which helps to provide a useful calibration check. ChlOE measurements compare well (within 6–8%) with the twice‐daily measurements from the Aura Microwave Limb Sounder and with 2010 measurements from the Submillimeter‐Wave Limb‐Emission Sounder. Key Points: A new ground‐based microwave instrument has been deployed at Mauna Kea to measure stratospheric ClO With the new instrument, it is now possible to simultaneously measure diurnal variations in ClO and O3 This instrument will extend the ClO measurement time series from Mauna Kea that began in 1992